AMINO AND MERCAPTO-SILICA HYBRID FOR Cd(II) ADSORPTION IN AQUEOUS SOLUTION - Buhani Buhani; Narsito Narsito; Nuryono Nuryono; Eko Sri Kunarti (Indonesian Journal of Chemistry, 2009)
Modification of silica gel with 3-aminopropyltrimethoxysilane and 3-mercaptopropyltrimethoxysilane through sol-gel technique producing amino-silica hybrid (HAS) and mercapto-silica hybrid (HMS), respectively, has been carried out using tetraethylorthosilicate (TEOS) as silica source. The adsorbents were characterized using infrared spectroscopy (IR), and X-ray energy dispersion spectroscopy (EDX). Adsorption of Cd(II) individually as well as its binary mixture with Ni(II), Cu(II), and Zn(II) in solution was performed in a batch system. Adsorption capacities of Cd(II) ion on adsorbent of silica gel (SG), HAS, and HMS are 86.7, 256.4 and 319.5 μmol/g with the adsorption energies are 24.60, 22.61 and 23.15 kJ/mol, respectively. Selectivity coefficient (α) of Cd(II) ion toward combination of Cd(II)/Ni(II), Cd(II)/Cu(II), and Cd(II)/Zn(II) ions on HAS adsorbent is relatively smaller than those on HMS adsorbent which has α > 1.